2004
DOI: 10.2337/diacare.27.2.491
|View full text |Cite
|
Sign up to set email alerts
|

Elevated White Blood Cell Count in Subjects With Impaired Glucose Tolerance

Abstract: OBJECTIVE -Impaired glucose tolerance (IGT) and impaired fasting glucose (IFG) differ in their risk of all-cause and cardiovascular mortality, but previous cross-sectional studies have suggested little difference in their levels of lipids or blood pressure. We compared the white blood cell (WBC) count between subjects with IFG and IGT.RESEARCH DESIGN AND METHODS -The subjects were 4,720 nondiabetic Japanese men aged 24 -84 years. Based on the 75-g oral glucose tolerance test, the subjects were classified into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 37 publications
6
68
1
1
Order By: Relevance
“…This is in agreement with the findings that WBC count is associated with insulin resistance [20,21], blood pressure [22], insulin concentration [22], triglyceride [22], and the components of MS [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the findings that WBC count is associated with insulin resistance [20,21], blood pressure [22], insulin concentration [22], triglyceride [22], and the components of MS [23].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, total WBC count was associated with postprandial 2 h glucose concentration, however, it was not associated with fasting glucose concentration. WBC count was independently related to postchallenge 2 h glucose concentration [21], and another inflammatory marker C-reactive protein (CRP) level is more strongly associated with postchallenge glucose than with fasting glucose in nondiabetic subjects [28]. According to previous studies, IL-6 increases postprandially, which is in parallel with glucose [29].…”
Section: Discussionmentioning
confidence: 94%
“…There is a strong association between obesity and leukocytosis, particularly of the myeloid lineage ( 6,28 ). A recent pioneering study has shown that MPC proliferation and monocytosis drive macrophage accumulation and insulin resistance in obesity ( 4 ).…”
Section: Hematopoietic Abca1 Deletion Results In Myelopoiesis and Monmentioning
confidence: 99%
“…The study by Vozarova et al, 2002 reported that there is relationship between WBC and diabetes mellitus as a result of increased inflammatory mediators. Inflammatory agents, insulin and human blood components form a critical signal for any abnormalities, resulting in invasion by foreign agents and/or inflammation (Ohshita et al, 2004). These latter factors can induce defense mechanisms and contribute to changes in levels of blood parameters, including mean white blood cell count, mean platelet count, and phagocyte percentage (Weyer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%